Real-time Packet Behavior Response in Socket Application - Prathap, M; Thanamani, AS (International Journal of Computer Sciences and Engineering, 2025)
The administrator has to know the network bandwidth and other resources that are used for accounting and auditing. This creates an emphasis to monitor network traffic and conduct analysis to ensure smooth operations performed routinely. Time is an important factor, which contributes to the variations of packet flow. flexible and allows powerful filters during or after capture to isolate traffic by specific node, protocol, and packet content In this paper, initially, the packet movement in the network was monitored with only hypertext transfers using HTTP. The same movement was analyzed with respect to other file transfer applications. The number of file downloads between the HTTP server and clients are also varied to follow the behavior of data. We also designed and developed multithreaded socket applications using java which was again monitored and analyzed using the above methodology. We compared the reading and the experimental results shows that the developed application outperforms in terms of packet acceleration compared to the previous ones.